Cytometric patterns reveal growth states of Shewanella putrefaciens. Issue 3 (3rd September 2014) - Melzer, Susanne; Winter, Gudrun; Jäger, Kathrin; Hübschmann, Thomas; Hause, Gerd; Syrowatka, Frank; Harms, Hauke; Tárnok, Attila; Müller, Susann
Summary Bacterial growth is often difficult to estimate beyond classical cultivation approaches. Low cell numbers, particles or coloured and dense media may disturb reliable growth assessment. Further difficulties appear when cells are attached to surfaces and detachment is incomplete. Therefore, flow cytometry was tested and used for analysis of bacterial growth on the single‐cell level. Shewanella putrefaciens was cultivated as a model organism in planktonic or biofilm culture. Materials of smooth and rough surfaces were used for biofilm cultivation. Both aerobic and anaerobic as well as feast and famine conditions were applied. Visualization of growth was also done using Environmental Scanning and Phase Contrast Microscopy. Bioinformatic tools were applied for data interpretation. Cytometric proliferation patterns based on distributions of DNA contents per cell corresponded distinctly to the various lifestyles, electron acceptors and substrates tested. Therefore, cell cycling profiles of S. putrefaciens were found to mirror growth conditions. The cytometric patterns were consistently detectable with exception of some biofilm types whose resolution remained challenging. Corresponding heat maps proved to be useful for clear visualization of growth behaviour under all tested conditions. Therefore, flow cytometry in combination with bioinformatic tools proved to be powerful means to determine various growth states of S. putrefaciens, even in constrained environments. The approach is universal and will also be applicable for other bacterial species.